The Development of Vocabulary Learning Achievement Using Activity Based Learning for Prathom Suksa 2 Students of Bannongkaeprachasun School - Sripuumma, Niramon; Thienpermpool, Dr.Patteera (Journal of Dhamma for Life, 2024)
The purposes of the research were to : 1) compare vocabulary learning achievement before and after using activity-based learning of prathom suksa 2 students of Bannongkaeprachasun School; 2) study the opinions of prathomsuksa 2 students of Bannongkaeprachasun School towards learning English vocabulary using activity-based learning. The sample group consisted of grade 2 students at Bannongkaeprachasan School. Kanchanaburi Province, semester 1, academic year 2023, number of 11 people, which were drawn from convenience random sampling. The duration of the experiment was four weeks. The instruments used for this research consisted of 1) lesson plans with activity based learning technique; 2) An English vocabulary achievement test; and 3) a questionnaire on opinions towards activity-based learning. The mean, standard deviation and t-test of dependent sample was used to analyzed the student’s vocabulary learning achievement.